Effects of remote ischemic conditioning on sleep complaints in Parkinson's disease–rationale, design, and protocol for a randomized controlled study - Ji, Qiling; Wang, Xuemei; Zhao, Wenbo; Wills, Melissa; Yun, Ho Jun; Tong, Yanna; Cai, Lipeng; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2022)
Objective Sleep disturbances are common non-motor symptoms of Parkinson's disease. The symptoms affect the quality of patients' life by impeding normal sleep cycles and causing excessive daytime sleepiness. Remote Ischemic Conditioning (RIC) is a therapy often used for ischemic stroke patients to minimize infarct size and maximize post-stroke neurological function. Animal experiments have shown that RIC plays a protective role for retinal ganglion cells and other critical areas of the brain of Parkinson's disease. However, whether RIC improves excessive daytime sleepiness (EDS) for patients with Parkinson's disease remains to be determined. Methods This is a single-center, double-blind, and randomized controlled trial, which includes patients with Parkinson's disease with EDS. All recruited patients will be randomly assigned either to the RIC or the control group (i.e., sham-RIC) with 20 patients in each group. Both groups receive RIC or sham-RIC treatment once a day for 28 days within 24 h of enrollment. Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Parkinson Disease Sleep Scale-2 (PDSS-2), Parkinson's Disease Questionnaire39 (PDQ39) score scales, and adverse events, such as inability to tolerate the treatment leading to suspension of the study or objective signs of tissue or neurovascular injury caused by RIC and/or sham-RIC are evaluated at 7, 14, 28, and 90 days after enrollment. Results The primary goal of this study is to assess the feasibility of the treatments in patients with Parkinson's disease by measuring serious RIC-related adverse events and any reduced incidence of adverse events during the trial and to study potential efficacy, improvement of patients' excessive daytime sleepiness, quality of life-based on ESS, PSQI, PDSS-2, and PDQ39 scores. The secondary goal is to confirm the safety of the treatments. Conclusion This study is a prospective randomized controlled trial to determine the safety, feasibility, and potential efficacy of RIC for patients with Parkinson's disease associated with EDS.